2007
DOI: 10.1007/s10531-007-9288-x
|View full text |Cite
|
Sign up to set email alerts
|

In situ collection of endangered arbuscular mychorrhizal fungi in a Mediterranean UNESCO Biosphere Reserve

Abstract: We report the establishment of the Wrst in situ collection of beneWcial symbiotic microorganisms (arbuscular mycorrhizal fungi) in the world, located in an integrally protected area of coastal sand dunes, within the UNESCO Biosphere Reserve "Selva Pisana", in Tuscany, Italy. In this collection the genus Scutellospora, which has been reported to be threatened by anthropogenic disturbance, was a regular component of Ammophila arenaria and Helichrysum stoechas rhizospheres, and was represented by two species: Scu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Our results report the occurrence of Scutellospora persica spores in the well preserved Spanish Mediterranean coastal sand dunes. This species has been recently recovered in the northwestern coast of Italy (Turrini et al, 2008) and had previously been described from other sand dunes (Koske and Walker, 1985;Blaszkowski and Tadych, 1997;Selvam and Mahadevan, 2002;Rodríguez-Echevarria and Freitas, 2006).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our results report the occurrence of Scutellospora persica spores in the well preserved Spanish Mediterranean coastal sand dunes. This species has been recently recovered in the northwestern coast of Italy (Turrini et al, 2008) and had previously been described from other sand dunes (Koske and Walker, 1985;Blaszkowski and Tadych, 1997;Selvam and Mahadevan, 2002;Rodríguez-Echevarria and Freitas, 2006).…”
Section: Discussionmentioning
confidence: 80%
“…According to Turrini et al (2008) the diversity of the non Glomus fungi (like species belonging to the Gigasporaceae group) recovered from the soils is low in ecosystems with high anthropogenic disturbance. In our work, spores from species of Gigaspora and Scutellospora, when present, were directly extracted in the field but not after a short trap culture cycle.…”
Section: Discussionmentioning
confidence: 99%
“…This result is important because for these three plant species the beneficial effect of mycorrhiza is not always seen as enhanced plant growth, which can depend on the substrate used. Under natural conditions these plants are always forming AM symbioses (Giovannetti 1985;Little and Maun 1996;Kowalchuk et al 2002;Maremmani et al 2003;Rodríguez-Echevarria et al 2007;Turrini et al 2008). The beneficial aspects of the symbiosis might also be related to the enhanced ability of mycorrhizal plants to tolerate sea water flooding episodes, and this could be the most important characteristic for their persistence in the front line of coastal sand dunes.…”
Section: Discussionmentioning
confidence: 99%
“…Harsh abiotic conditions like burial by drifting sand, wind, heat fluctuations, intense sunlight, nutrient deficient soils and salt spray determine the establishment and persistence of a vegetal cover (Koske et al 1996). Psammophilic plants have adapted to grow in sand under such conditions, and in natural ecosystems the roots of most of these plants are found to be associated with arbuscular mycorrhizal (AM) fungi (Koske and Tews 1987;Beena et al 2000;Koske et al 2004;Turrini et al 2008;Camprubi et al 2010). Arbuscular mycorrhizal fungi are thus present in sand dune systems throughout the world and they are known to significantly contribute to the development of the plant community and to the stabilization of the sand dune both indirectly, by improving nutrients and water uptake, and directly, by improving soil structure and stability through the formation of sand grain aggregates (Jakobsen 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was reported that the use of indigenous AM had advantages as the microorganism was able to establish and develop well in situ environment as well as its better ability to compete with existing soil microbes compared with introduced AM (Turrini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%